Flipped Classroom Dalam Pembelajaran Matematika: Tantangan Dan Peluang Untuk Pembelajaran Mandiri - Hukom, Julham (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to explore the challenges and opportunities provided by the implementation of the flipped classroom model in mathematics learning, especially to support students' independent learning. The method used in this study is the Integrative Literature Review, which includes five stages, namely compiling review questions, collecting literature data, critical assessment of literature data, thematic data extraction and analysis, and presenting findings and discussions. The findings indicate that flipped classrooms have great potential to increase student engagement, support independent learning, and develop problem-solving skills. However, the main challenges faced are students' less than optimal independent skills, unequal access to technology, and difficulties in time management. This study recommends providing training to students in managing independent learning, as well as strengthening equitable access to technology across students. Further research is recommended to examine the implementation of flipped classrooms in various educational settings and explore more specific innovative solutions to address existing challenges.